Population Connectivity of the Highly Migratory Shortfin Mako (Isurus oxyrinchus Rafinesque 1810) and Implications for Management in the Southern Hemisphere - Corrigan, Shannon; Lowther, Andrew D.; Beheregaray, Luciano B.; Bruce, Barry D.; Cliff, Geremy; Duffy, Clinton A.; Foulis, Alan; Francis, Malcolm P.; Goldsworthy, Simon D.; Hyde, John R.; Jabado, Rima W.; Kacev, Dovi; et al. (Frontiers in Ecology and Evolution, 2018)
In this paper we combine analyses of satellite telemetry and molecular data to investigate spatial connectivity and genetic structure among populations of shortfin mako (Isurus oxyrinchus) in and around Australian waters, where this species is harvested in recreational and commercial fisheries. Mitochondrial DNA data suggest matrilineal substructure across hemispheres, while nuclear DNA data indicate shortfin mako may constitute a globally panmictic population. There was generally high genetic connectivity within Australian waters. Assessing genetic connectivity across the Indian Ocean basin, as well as the extent that shortfin mako exhibit sex biases in dispersal patterns would benefit from future improved sampling of adult size classes, particularly of individuals from the eastern Indian Ocean. Telemetry data indicated that Australasian mako are indeed highly migratory and frequently make long-distance movements. However, individuals also exhibit fidelity to relatively small geographic areas for extended periods. Together these patterns suggest that shortfin mako populations may be genetically homogenous across large geographical areas as a consequence of few reproductively active migrants, although spatial partitioning exists. Given that connectivity appears to occurring at different scales, management at both the national and regional levels seems most appropriate.